Essays in honor of Subal Kumbhakar - Parmeter, Christopher F.; Tsionas, Mike G.; Wang, Hung-Jen (Advances in econometrics, 2024)
Volume 46 of Advances in Econometrics presents essays in honor of Subhal Kumbhakar. His influence on the applied productivity and efficiency profession is legion, as evidenced by his voluminous body of research, must read textbook and attendance at sessions where he is presenting or his work is featured. Subal's oeuvre continues to grow, his ability to move the applied econometric and productivity literature forward never stalling and his charismatic smile always there to cheer up colleagues and friends on a gloomy day. It is the editor's distinct privilege to gather this collection of papers that honors Subal's many accomplishments, drawing further attention to the various areas of scholarship that he has touched. Advances in Econometrics publishes original scholarly econometrics papers with the intention of expanding the use of developed and emerging econometric techniques by disseminating ideas on the theory and practice of econometrics throughout the empirical economic, business, and social science literature. Annual volume themes, selected by the Series Editors, are their interpretation of important new methods and techniques emerging in economics, statistics, and the social sciences.